Hubungan Mekanisme Koping dengan Kualitas Hidup pada Klien Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Kaliwates-Jember - Putri Hidayatur Rochmah; Hanny Rasni; Kholid Rosyidi Muhammad Nur (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Type 2 Diabetes Mellitus (T2DM) is one of the progressive chronic diseases that cause various complications. Complications that are often experienced by T2DM clients such as foot injuries can affect the quality of life. One of the factors influencing the quality of life is a coping mechanism. This study aimed to analyze the relationship between coping mechanisms and the quality of life of clients of T2DM in the working area of ​​Kaliwates Primary Health Center, Jember. The design of this research was analytical with a cross-sectional approach. Respondents in this study were 84 and obtained by a purposive sampling technique. The data collection method used the Cope Inventory and DQOL (Diabetes Quality of Life) questionnaire. The data analysis used Spearman correlation test with a significance level of 0.05. The results of the study showed that the most used coping was emotional-focused coping with an average value was 3.02 and the majority of respondents had a high quality of life of 67 respondents (79.8%). There is no correlation between coping mechanisms and the quality of life of clients of T2DM in the work area of ​​Kaliwates Primary Health Center, Jember (p-value = 0.273). Other factors such as anxiety, depression, physical activity, control of blood sugar, fatigue, and stress need to be assessed to improve the quality of life for clients of T2DM.